2016
DOI: 10.5433/1679-0359.2016v37n5p3361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of grazing beef cows receiving supplements with different protein contents

Abstract: The aim of this study was to evaluate the effects of supplementation with different crude protein contents on the productive performance of grazing beef cows during post-calving. Thirty-six beef cows, with age and average body weight of 5 years and 490±17.9 kg, respectively, were used. The experimental design was completely randomized. The treatments were: control = cows received only mineral mixture ad libitum; supplemented = cows received 1 kg d -1 of supplement containing 80, 200, or 320 g crude protein (CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
2
5
0
2
Order By: Relevance
“…Feed supplementation can reduce the nutritional stress and enhance the onset of ovarian cyclicity after calving. Bos indicus cows have a greater ability to retain and deposit energy, and supplementation of grazing cows improves the nutrient utilization (Lopes et al 2016). The combination of cow and calf performance in a Zebu herd in Africa management under similar conditions of the present study showed the best results when the dams were treated before and after calving with supplement content cottonseed cake and molasses (Sidibé-Anago et al, 2008).…”
Section: Resultssupporting
confidence: 52%
“…Feed supplementation can reduce the nutritional stress and enhance the onset of ovarian cyclicity after calving. Bos indicus cows have a greater ability to retain and deposit energy, and supplementation of grazing cows improves the nutrient utilization (Lopes et al 2016). The combination of cow and calf performance in a Zebu herd in Africa management under similar conditions of the present study showed the best results when the dams were treated before and after calving with supplement content cottonseed cake and molasses (Sidibé-Anago et al, 2008).…”
Section: Resultssupporting
confidence: 52%
“…In this study, NEFA concentrations were not affected by supplementation and these levels at calving indicate a higher adipose tissue rate of lipolysis [29,30]. The NEFA post-partum concentrations were lower compared to parturition, and remained at basal concentrations throughout the experimental period, which suggests the recovery of animals' nutritional status.…”
Section: Discussionmentioning
confidence: 51%
“…In this study, NEFA concentrations were not affected by supplementation and these levels at calving indicate a higher adipose tissue rate of lipolysis [43,44]. The NEFA post-partum concentrations were lower compared to parturition, and remained at basal concentrations throughout the experimental period, which suggests the recovery of animals' nutritional status.…”
Section: Discussionmentioning
confidence: 51%